Intermediate Algebra (12th Edition)

Published by Pearson
ISBN 10: 0321969359
ISBN 13: 978-0-32196-935-4

Chapter 6 - Section 6.2 - Adding and Subtracting Rational Expressions - 6.2 Exercises: 18

Answer

$y-6$

Work Step by Step

$\frac{y^{2}}{y+6}-\frac{36}{y+6}=\frac{y^{2}-36}{y+6}=\frac{(y-6)(y+6)}{y+6}=(y-6)\times\frac{y+6}{y+6}=(y-6)\times1=y-6$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.